PENYULUHAN TENTANG PERANAN ISTRI DALAM MANAJEMEN KEUANGAN RUMAH TANGGA BAGI KELUARGA MUDA PURI NIRWANA PANDANWANGI RT 3 RW 3 KELURAHAN PANDANWANGI KECAMATAN BLIMBING KOTA MALANG - Shinta Maharani Trivena; Ellyn Eka Wahyu; Erlangga Andi Sukma; Farida Akbarina; Siti Nurbaya (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
Community Service Activities was held on August 26, 2017 in Puri Nirwana Pandanwangi Jl Kalisari Gang Makam RT 03 RW 03 Pandanwangi Blimbing, Malang. This activity is divided into several namely the preparation stage includes the preparation of places and events, the stage of delivery of materials, the discussion phase, and the closing stage. The goal is to open the participants' awareness on the importance of household financial management for the future of the family, strengthen the commitment to discipline in managing expenditure, strengthening the relationship between State Polytechnic of Malang with society at large. Success in the community service is apparent after the socialization event is completed that some residents proposed to be held monthly arisan as a substitute to save in the bank and strengthen the relationship between housing residents. All participants are quite easy in understanding the material provided.